Study of carbapenem resistance in patients admitted to MICU in a tertiary care hospital - Shaji, Eby P.; Iravane, Jyoti A.; Harbade, Mangala S.; Gaikwad, Anil A. (International Journal of Research in Medical Sciences, 2025)
Background: Carbapenem Resistance is defined as gram negative bacteria that are resistant to one or all of the following carbapenems: ertapenem, meropenem, imipenem or doripenem. Recognizing the risk of resistance to carbapenem especially in the most vulnerable patients and the early detection of specific carbapenem-resistance mechanisms are critical to reducing the risk of mortality, length of hospitalization and associated costs. So, this study is done to detect carbapenem resistance in patients admitted in MICU. Methods: A Retrospective study was carried out for one year from period of January 2023-January 2024 in the Department of Microbiology, Government Medical College, Aurangabad. Total 1941 samples were received from patients admitted in the medical intensive care unit (MICU). The isolates were identified using standard microbiological methods. Antimicrobial susceptibility was performed using the Kirby-Bauer disc diffusion technique and interpreted as per CLSI 2023 standards. Results: Out of 1941 samples, total gram-negative isolates were 775 (40%), 478 samples were sterile and rest were gram positive organism. Out of gram-negative organism Acinetobacter baumannii (26.58%), Escherichia coli (11.74%), Klebsiella pneumoniae (32.25%) and Pseudomonas aeruginosa (29.41%) were isolated. In case of Acinetobacter, Carbapenem resistant is high and is around 90%, in Escherichia coli it is 74%, in Klebsiella and Pseudomonas it is 83% and 44% respectively. Conclusions: In our study Acinetobacter baumannii shows high carbapenem resistance. The efficient ways to avoid infection include strict adherence to infection prevention and control practices like hand hygiene techniques and bundle care approach.